A different background for Isaiah 22:15-25 presents an alternative paradigm: disposing of political and religious opposition? - Auret, A. (Old Testament essays, 1993)
The historical context of prophetic texts is not always explicitly mentioned, simply because the original addressee/s form part of the context. The interpretation of such texts to a large extent depends on the (hypothetical) contexts ascribed to them. This is also the case with Isaiah 22:15-22. A slight adjustment of the context generally ascribed to this pericope and a reconstruction of the possible political environment result in a different interpretation. Instead of the pericope being a paradigm for restoring just officials, it seems to be a paradigm for disposing of religious and political opponents.